Diagnostic accuracy of faecal immunochemical test for screening individuals with a family history of colorectal cancer. Issue 7 (20th August 2013) - Ng, S. C.; Ching, J. Y. L.; Chan, V.; Wong, M. C. S.; Suen, B. Y.; Hirai, H. W.; Lam, T. Y. T.; W Lau, J. Y.; Ng, S. S. M.; Wu, J. C. Y.; Chan, F. K. L.; Sung, J. J. Y.
Summary Background The role of a faecal immunochemical test (FIT) in screening individuals with a positive family history of colorectal cancer (CRC) is not clear. Aim To assess the diagnostic accuracy of FIT using colonoscopy findings as the gold standard in identifying colorectal neoplasms. Methods We analysed data from 4539 asymptomatic subjects aged 50–70 years who had both colonoscopy and FIT (Hemosure; W.H.P.M., Inc, El Monte, CA, USA) at our bowel cancer screening centre between 2008 and 2012. A total of 572 subjects (12.6%) had a family history of CRC. Our primary outcome was the sensitivity of FIT in detecting advanced neoplasms and cancers in subjects with a family history of CRC. A family history of CRC was defined as any first‐degree relative with a history of CRC. Results Among 572 subjects with a family history of CRC, adenoma, advanced neoplasm and cancer were found at screening colonoscopy in 29.4%, 6.5% and 0.7% individuals, respectively. The sensitivity of FIT in detecting adenoma, advanced neoplasm and cancer was 9.5% [95% confidence interval (CI), 5.7–15.3], 35.1% (95% CI, 20.7–52.6) and 25.0% (95% CI, 1.3–78.1), respectively. Among FIT‐negative subjects who have a family history of CRC, adenoma was found in 152 (29.6%), advanced neoplasm in 24 (4.7%) and cancer in 3 (0.6%) individuals. Conclusion Compared with colonoscopy, FIT is more likely to miss advanced neoplasms or cancers in individuals with a family history of CRC.